If we build it, will they come? Perspectives on pharmacy-based naloxone among family and friends of people who use opioids: a mixed methods study - Susannah Slocum; Jenny E. Ozga; Rebecca Joyce; Alexander Y. Walley; Robin A. Pollini (BMC, 2022)
Abstract Background Expanding access to the opioid antagonist naloxone to reduce overdose mortality is a public health priority in the United States. Naloxone standing orders (NSOs) have been established in many states to increase naloxone dispensing at pharmacies, but increased pharmacy access does not ensure optimal uptake among those likely to witness an overdose. In a prior statewide purchase trial, we documented high levels of naloxone access at Massachusetts pharmacies under a statewide NSO. In this study, we characterize barriers to pharmacy-based naloxone uptake among potential opioid overdose "bystanders" (friends or family of people who use opioids) that may be amenable to intervention. Methods Eligible bystanders were Massachusetts residents ≥ 18 years of age, did not use illicit opioids in the past 30 days, and knew someone who currently uses illicit opioids. We used a sequential mixed methods approach, in which a series of semi-structured qualitative interviews (N = 22) were conducted April-July 2018, to inform the development of a subsequent quantitative survey (N = 260), conducted February-July 2020. Results Most survey participants (77%) reported ever obtaining naloxone but few (21%) attempted to purchase it at a pharmacy. Qualitative participants revealed that barriers to utilizing the NSO included low perceived risk of overdose, which was rooted in misconceptions regarding the risks of prescription opioid misuse, denial about their loved one's drug use, and drug use stereotypes; inaccurate beliefs about the impact of naloxone on riskier opioid use; and concerns regarding anticipated stigma and confidentiality. Many participants had engaged in mutual support groups, which served as a source of free naloxone for half (50%) of those who had ever obtained naloxone. Conclusions Despite high levels of pharmacy naloxone access in Massachusetts, few bystanders in our study had attempted to obtain naloxone under the NSO. Low perceived risk of overdose, misinformation, stigma, and confidentiality were important barriers to pharmacy naloxone uptake, all of which are amenable to intervention. Support groups provided a setting for addressing stigma and misinformation and provided a discreet and comfortable setting for naloxone access. Where these groups do not exist and for bystanders who do not participate in such groups, pharmacies are well-positioned to fill gaps in naloxone availability.